2015
DOI: 10.1371/journal.pone.0140750
|View full text |Cite|
|
Sign up to set email alerts
|

IL-22/STAT3-Induced Increases in SLURP1 Expression within Psoriatic Lesions Exerts Antimicrobial Effects against Staphylococcus aureus

Abstract: Background SLURP1 is the causal gene for Mal de Meleda (MDM), an autosomal recessive skin disorder characterized by diffuse palmoplantar keratoderma and transgressive keratosis. Moreover, although SLURP1 likely serves as an important proliferation/differentiation factor in keratinocytes, the possible relation between SLURP1 and other skin diseases, such as psoriasis and atopic dermatitis, has not been studied, and the pathophysiological control of SLURP1 expression in keratinocytes is largely unknown.Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 33 publications
2
24
0
5
Order By: Relevance
“…The expression of Defb3 mRNA is strikingly diminished in patients with recurrent S. aureus infections 26 suggesting its importance in controlling the severity of S. aureus infections. The secreted lymphocyte antigen-6/urokinase-type plasminogen activator receptor related protein-1 (SLURP1) encoded by Slurp1 , has been shown to induce proliferation of keratinocytes and suppression of growth of S. aureus 27 . Hence, our finding that the induction of Slurp1 and Defb14 in tape stripped skin is regulated by IL-22 demonstrates that IL-22 possesses a pleiotropic role in the control of S. aureus infection in mechanically injured skin of mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of Defb3 mRNA is strikingly diminished in patients with recurrent S. aureus infections 26 suggesting its importance in controlling the severity of S. aureus infections. The secreted lymphocyte antigen-6/urokinase-type plasminogen activator receptor related protein-1 (SLURP1) encoded by Slurp1 , has been shown to induce proliferation of keratinocytes and suppression of growth of S. aureus 27 . Hence, our finding that the induction of Slurp1 and Defb14 in tape stripped skin is regulated by IL-22 demonstrates that IL-22 possesses a pleiotropic role in the control of S. aureus infection in mechanically injured skin of mice.…”
Section: Resultsmentioning
confidence: 99%
“…We observed a decrease in the expression of Slurp1 and Defb14 . Both of these proteins have been shown to suppress the growth of S. aureus 26, 27 . These findings suggest that IL-22 acts pleiotropically to inhibit S. aureus infections.…”
Section: Discussionmentioning
confidence: 99%
“…SLURP‐1 can act as allosteric antagonist of the α7nAChR but has also been demonstrated to activate metabotropic‐signalling pathways (Lyukmanova et al, ). SLURP‐1 is secreted at mucosal sites and has also been shown to have both immunomodulatory (Moriwaki et al, ) and antimicrobial properties (Moriwaki et al, ). In addition, SLURP‐1 has been found to inhibit proliferation of oral keratinocytes (Lyukmanova et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…SLURP-1 is secreted at mucosal sites and has also been shown to have both immunomodulatory (Moriwaki et al, 2007) and antimicrobial properties (Moriwaki et al, 2015). In addition, SLURP-1 has been found to inhibit proliferation of oral keratinocytes (Lyukmanova et al, 2016).…”
mentioning
confidence: 99%
“…A severe form of palmoplantar keratoderma has been observed in SLURP1‐deficient mice , and SLURP1 mutations were found to be the underlying defect in mal de Meleda in humans . Recently, it was shown that expression of SLURP1 was upregulated in a mouse model of psoriasis induced by imiquimod, suggesting that SLURP1 may also play a role in human psoriasis . This protein features the three‐finger folded structure which has been detected in a family of neurotoxins derived from snakes and frogs.…”
Section: Introductionmentioning
confidence: 99%